Treating rheumatoid arthritis in Zanzibar: a cost effectiveness study comparing conventional, biologic, and targeted-synthetic disease modifying anti-rheumatic drugs - Sanaa S. Said; Sanaa S. Said; Sanaa S. Said; Sanaa S. Said; Sanaa S. Said; Melf-Jakob Kühl; Melf-Jakob Kühl; Bjorg-Tilde Svanes Fevang; Bjorg-Tilde Svanes Fevang; Tone Wikene Nystad; Kjell Arne Johansson; Kjell Arne Johansson (Frontiers in Medicine)
Rheumatoid arthritis is a chronic inflammatory joint disease with low treatment coverage in sub-Saharan Africa. Effective treatment strategies are available. We aimed to evaluate the cost effectiveness of six disease modifying anti-rheumatic drug (DMARD) treat-to-target treatment strategies for patients with rheumatoid arthritis in Zanzibar. A Markov model was used to calculate the cost-effectiveness of various DMARD strategies in the treatment of rheumatoid arthritis over a 3-year period. A health-provider perspective was used and only outpatient costs were considered. The Clinical Disease Activity Index (CDAI) was utilized for measurement of efficacy and values were obtained from literature. Quality Adjusted Life Years (QALYs) were obtained from 122 patients attending the rheumatology clinic at Mnazi Mmoja Hospital. Data on costs were obtained from the central medical stores and hospital administration. Treatment strategies were given in sequential approach based on treat to target goals of therapy. This included methotrexate monotherapy, methotrexate + sulfasalazine + hydroxychloroquine, methotrexate followed by one or two biologic/targeted-synthetic DMARDs (b/tsDMARDs). Probabilistic and one way sensitivity analysis were performed. Scenario analysis was undertaken comparing drug prices from India and Scandinavia. Costs of therapy/patient/3 years ranged from USD 634 for methotrexate monotherapy and USD 5011 for methotrexate and two consecutive b/tsDMARDs. The highest and lowest effects were 2.209 and 2.079 QALYs gained from methotrexate therapy + two consecutive b/tsDMARDs and methotrexate monotherapy, respectively. From a healthcare provider perspective methotrexate monotherapy was the cost-effective option at a willingness to pay of USD 282. Pairwise comparison also favored methotrexate monotherapy as the feasible option. We found that increasing the willingness to pay led to a change in the most acceptable option from methotrexate monotherapy to methotrexate followed by b/tsDMARD. Methotrexate monotherapy is the cost-effective option for the management of rheumatoid arthritis in Zanzibar. Other options may be feasible if the willingness to pay threshold is increased or the drug prices are lowered, particularly for the b/tsDMARDs.